Stifling the Wind: California Environmental Quality Act and Local Permitting - Troxler, Brian (Columbia Journal of Environmental Law, 2019)
At the turn of the millennium, California led the nation in installed wind energy capacity. California had over 1600 megawatts (“MW”) of capacity, representing a majority of the nation’s 2472 MW. The second most developed state had only had seventeen percent of California’s capacity. However, since 2000, wind capacity in the United States has increased twentyfold to almost 50,000 MW, while capacity in California has less than tripled. Although many factors contribute to differing rates wind energy development across the United States, California’s decentralized siting and arduous environmental evaluation requirements should bare blame. Though California still maintains the third most installed wind energy capacity, despite ranking nineteenth in terms of total wind generating potential, it still has 34,000 MW of uptapped on-shore economic wind potential. In-state wind resources have the potential to meet 39.4% of the State’s current energy needs but currently only provide 3.3%. Focusing on California’s relative wind potential understates California’s ability to develop practically viable wind resources in the near future. Moreover, attributing California’s repressed growth solely to its relative amount of wind resources oversimplifies the issue and ignores the possibility that California’s regulatory regime and its implementation may be less accommodating to wind energy development than regimes in other states. California allows local governments to site commercial wind projects, delegating this technical and complicated task to planning committees that are often not specialized. The California Environmental Quality Act (“CEQA”) further complicates this process. Under CEQA, the local government must analyze the environmental impacts of proposed projects and consider those impacts in deciding whether to issue a permit. The combination of decentralized siting and stringent environmental evaluation shrouds the cost, outcome, and timeline of the permitting process in uncertainty, chilling investment in new capacity. However, environmental evaluation procedures should clearly not be discarded. Wind projects may damage wildlife habitats or kill birds and bats, especially when poorly sited. Towering wind turbines dominate rural landscapes, sometimes disrupting aesthetically important sites or causing noise pollution. Despite these potential impacts, wind energy benefits the environment substantially by reducing pollutant emissions and water consumption. Thus, the challenge is to site wind projects efficiently in less environmentally sensitive areas. The California state government should take a significant step towards this goal by exercising its authority to site wind energy projects and by conducting environmental review of those projects in a uniform, timely, and predictable manner.